B, P, and S heteroatom doped, bio- and hemo-compatible 2D graphitic-carbon nitride (g-C3N4) with antioxidant, light-induced antibacterial, and bioimaging endeavors - KOCA, ATIF (My University, 2023)
The synthesis of two-dimensional (2D) graphiticg-C3N4and heteroatom-doped graphitic H@g-C3N4(H: B, P, or S) particles were successfully done using melamine as source compounds and boric acid, phosphorous red, and sulfur as doping agents. The band gap values of 2Dg-C3N4, B50@g-C3N4, P50@g-C3N4, and S50@g-C3N4structures were determined as 2.90, 3.03, 2.89, and 2.93 eV, respectively. The fluorescent emission wavelengths of 2Dg-C3N4, B50@g-C3N4, P50@g-C3N4, and S50@g-C3N4structures were observed at 442, 430, 441, and 442 nm, respectively upon excitation atλEx= 325 nm. There is also one additional new emission wavelength was found at 345 nm for B50@g-C3N4structure. The blood compatibility test results ofg-C3N4, B50@g-C3N4, P50@g-C3N4, and S50@g-C3N4structures revealed that all materials are blood compatible with 90% blood clotting indices at 100μg ml-1concentration. The cell toxicity of the prepared 2D graphitic structures were also tested on L929 fibroblast cells, and even the heteroatom doped hasg-C3N4structures induce no cytotoxicity was observed with >91% cell viability even at 250μg ml-1particle concentration with the exception of P50@g-C3N4which as >75 viability. Moreover, for 2Dg-C3N4, B50@g-C3N4, and S50@g-C3N4constructs, even at 500μg ml-1concentration, >90% cell viabilities was monitored. As a diagnostic material, B50@g-C3N4was found to have significantly high penetration and distribution abilities into L929 fibroblast cells granting a great potential in fluorescence imaging and bioimaging applications. Furthermore, the elemental doping with B, P, and S ofg-C3N4were found to significantly increase the photodynamic antibacterial activity e.g. more than half of bacterial elimination by heteroatom-doped forms ofg-C3N4under UVA treatment was achieved.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Biyomedikal Mühendisliği; Kimya; Temel Bilimler; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Information Systems, Communication and Control Engineering; Signal Processing; Biomedical Engineering; Chemistry; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, MEKANİK; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; MALZEME BİLİMİ, KOMPOZİTLER; MÜHENDİSLİK, BİYOMEDİKAL; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, MECHANICAL; ENGINEERING, ELECTRICAL & ELECTRONIC; MATERIALS SCIENCE, COMPOSITES; ENGINEERING, BIOMEDICAL; Biyomühendislik; Fizik Bilimleri; Genel Kimya; Genel Malzeme Bilimi; Malzemelerin mekaniği; Makine Mühendisliği; Elektrik ve Elektronik Mühendisliği; Bioengineering; Physical Sciences; General Chemistry; General Materials Science; Mechanics of Materials; Mechanical Engineering; Electrical and Electronic Engineering; B-; biocompatible/bloodcompatible and antibacterial 2D particles; P-; photo-active graphitic nitride; S-doped 2D g-C3N4